2020
DOI: 10.3847/1538-3881/ab84f2
|View full text |Cite
|
Sign up to set email alerts
|

TESS Reveals HD 118203 b to be a Transiting Planet

Abstract: The exoplanet HD118203 b, orbiting a bright (V=8.05) host star, was discovered using the radial velocity method by da Silva et al., but was not previously known to transit. Transiting Exoplanet Survey Satellite (TESS) photometry has revealed that this planet transits its host star. Nine planetary transits were observed by TESS, allowing us to measure the radius of the planet to be-+ R 1.136 J 0.028 0.029 , and to calculate the planet mass to be-+ M 2.166 J 0.079 0.074 6.134985 0.000030 0.000029 days and an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 98 publications
2
8
0
Order By: Relevance
“…A detailed analysis of transit probabilities for known RV exoplanets by Dalba et al (2019) resulted in a prediction of about three transit detections during the TESS primary mission. Our reporting of transits for two of the HD136352 planets, combined with the detected transit for HD118203b (Pepper et al 2020), brings the total number of RV planets revealed to be transiting in line with the Dalba et al (2019) predictions. Note that the TESS extended mission will likely lead to further transit detections of known RV planets whose orbital periods are longer than TESS observations of their host star during the primary mission.…”
Section: System Propertiessupporting
confidence: 72%
See 1 more Smart Citation
“…A detailed analysis of transit probabilities for known RV exoplanets by Dalba et al (2019) resulted in a prediction of about three transit detections during the TESS primary mission. Our reporting of transits for two of the HD136352 planets, combined with the detected transit for HD118203b (Pepper et al 2020), brings the total number of RV planets revealed to be transiting in line with the Dalba et al (2019) predictions. Note that the TESS extended mission will likely lead to further transit detections of known RV planets whose orbital periods are longer than TESS observations of their host star during the primary mission.…”
Section: System Propertiessupporting
confidence: 72%
“…The survey strategy of TESS thus provides a space-based means to systematically examine all of the known RV systems for potential transits of their planets that pass through inferior conjunction during the TESS observing window (Kane & von Braun 2008;Dalba et al 2019). This has been demonstrated through the transit detection of an additional planet in the piMensae system (Huang et al 2018) and the known RV planet in the HD118203 system (Pepper et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The PDF of stellar mass and age (and their correlated parameters) show bimodality, which can be seen in Figure A1. This type of bimodality has been observed in several recent studies (Grieves et al 2021;Ikwut-Ukwa et al 2020;Carmichael et al 2020Carmichael et al , 2021Pepper et al 2020) and it appears due to the degeneracy between the MIST isochrones in the region of T eff -log g * plane occupied by TOI-1789. The two peaks in the PDF are centered at a mass of 1.35 M (age = 4.15 Gyr) and 1.51 M (age = 2.71 Gyr) with the probability of 32% and 68%, respectively.…”
Section: Modelling the Host Starsupporting
confidence: 65%
“…This first-order acceleration parameter constitutes a lower limit for the semi-amplitude through (t f −t i )× γ/2 with t f and t i being the final and first timestamps. Following the Monte Carlo approach in Kane et al (2019) (see also Pepper et al 2020), Planet density (g cm −3 ) -1.3 ± 0.5 (M p sin i) c…”
Section: Resultsmentioning
confidence: 99%